Fungal Necromass Carbon Stabilizes Rhizosphere Soil Organic Carbon: Microbial Degradation Gene Insights Under Straw and Biochar - Haiyan Jiang; Duoji Wu; Jie Chen; Haoan Luan; Chunhuo Zhou; Xiaomin Zhao; Jianfu Wu; Qinlei Rong (Agronomy)
Microbial necromass carbon (MNC) is the dominant contributor to soil organic carbon (SOC). However, the contribution of MNC in different soil compartments to SOC sequestration has not been comprehensively studied, especially under the organic fertilizers input. To address this gap, we conducted a rice root box experiment by adding organic fertilizer (straw and straw biochar) and chemical fertilizer alone to red loamy paddy soil, respectively. We found that although SOC accumulation was stimulated by both biochar and straw in the rhizosphere, more substantial SOC was sequestered in the rhizosphere due to biochar addition (increased by 25.82% compared to straw addition). Additionally, the input of organic fertilizers resulted in varying degrees of MNC retention in the different soil compartments. Compared with that in bulk soil, fungal necromass carbon (FNC) content was reduced by 1.37% and 7.06%, and bacterial necromass carbon (BNC) content was reduced by 5.53% and 9.49% in the rhizosphere and hyphosphere, respectively, following straw addition. Conversely, the addition of biochar leads to a significant increase of FNC (increased by 2.92%) and BNC (increased by 2.00%) in the rhizosphere compared with bulk soil. However, straw addition also significantly enhanced SOC thermal stability within the rhizosphere and hyphosphere soils. Based on partial least squares path modeling, we found that SOC thermal stability was significantly and positively influenced by FNC, which was strongly associated with carbon degradation gene abundance. These results emphasize the critical role of soil compartments in SOC sequestration under organic fertilizer application and underscore the importance of FNC in enhancing SOC stability in the rhizosphere.